Pre-Service Teachers' Belief on Professional Development: A study on ESP Teacher - Aisyah Aisyah; Bayu Hendro Wicaksono (University of Muhammadiyah Malang, 2018)
Guskey (2002) asserted that professional development is seen as a beneficial practice to disclosed the change required in teachers profession. Indeed, teacher's belief is becoming one of the driving forces which led to the practice in regards. In fact, Some of the ESP instructors seem to find it difficult to deal with the practice of professional development. This is the situation happened in Language Center, the center of ESP program, at my institution. Although some research have been investigating the case of teacher belief within professional development, but little research conducted in ESP course at Indonesian Universities context. Thus, this present study is designed at finding 1) the pre-service teachers' beliefs in being professional language teachers in teaching ESP, and 2) the professional activities undertaken by the pre-service teachers to develop their professionalism in teaching ESP. Through the explanatory research, a chosen ESP pre-service teachers participated in this study. The data from it were generated from survey, observation and interview to have a saturated information. These methods were on purpose to validate the data. The finding showed that being professional language teachers has fallen on eight indicators which are different from some other related research. The finding also gave information on four types of famous activities undertaken by the pre-service teacher.